Hubungan Pelatihan, Beban Kerja, Motivasi dan Kepuasan Kerja dengan Kinerja Tenaga Kesehatan dalam Penemuan Kasus TB - Ronny Setiawati; Ratno Adrianto; Iwan M. Ramdan (Universitas Faletehan, 2025)
Tuberculosis (TB) cases detection is one of the main interventions in addressing this health problem, which the high or low rate of case detection can be brought on by several causes, such as the lack of performance of healthcare workers in detecting TB cases. The objective of this research was to examine how the performance of healthcare workers in detecting TB cases is related to training, workload, motivation, and job satisfaction. This quantitative research was conducted using a cross-sectional approach. Overall, a total of 77 health workers from Samarinda Public Health Center became the sample. The results of the chi-square test indicated that there was no relationship between training and the performance of TB healthcare workers. However, there was a relationship between the performance of TB healthcare workers and workload (p=0.043), motivation (p=0.000), and job satisfaction (p=0.000). The factor that significantly influenced the performance of TB healthcare workers was job satisfaction. Organizational leaders were expected to enhance employee satisfaction by providing a pleasant workplace.